Work-Life Quality of Teachers at Wat Tri Samakkee School under Samut Prakan Primary Educational Service Area Office 1 - พยุงวงษ์ สาธร; วงษ์เล็ก ภูษิตย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were to study and compare the quality of work-life of teachers at Wat Tri Samakkee School under the Samut Prakan Primary Educational Service Area Office 1, classified by personal factors. The population for this study consisted of 38 teachers at Wat Tri Samakkee. The research instrument was a questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.67 to 1.00 and a total reliability coefficient of 0.92. Data were analyzed using percentage, mean, and standard deviation, and mean comparison was conducted using mean comparison tables. The research findings revealed that the overall quality of work-life of teachers at Wat Tri Samakkee School was at a high level. The dimension with the highest mean was Work, followed by Social, Economic, and Personal dimensions, respectively. 2) Teachers who were different personal factors including gender, age, educational level, current position, academic standing, and work experience showed no significant difference in their overall quality of work-life.